PENGARUH HARGA TERHADAP MINAT BELI TIKET OBJEK WISATA AQUALAND KOTA SERANG - Mahmud Ali; Arif; Miftah Faiz Ali Ramdhani (LPPM STIA Banten, 2023)
The objectives of this study are to ascertain the cost of tickets for the Aqualand tourist attraction in Serang City, gauge consumer interest in purchasing tickets there, and ascertain the degree to which pricing affects consumer interest in purchasing tickets. Using probability sampling procedures to select a sample of 100 respondents, the study employs descriptive quantitative research methods. Based on the correlation coefficient interval (0.600 – 0.799), the Correlation Analysis results showed a r value of 0.747, indicating the presence of a substantial level of association. In the meantime, the price variable contributes 55.8%, according to the coefficient of determination value of 55.8%.Next, based on the correlation significance test findings utilizing the hypothesis t test, it is established that the estimated t value, or 11.119 > 1.661, is more than the t table. This demonstrates that Ha is approved and H0 is refused. Price essentially has a favorable and considerable impact on interest in purchasing tickets for Serang City's Aqualand tourist attraction.